ASSESSMENT OF KNOWLEDGE ON PHLEBITIS AND ITS ASSOCIATED FACTORS AMONG NURSING STUDENTS IN SELECTED COLLEGE OF NURSING IN WEST BENGAL - Maity, Soma; Kundu, Mousumi (International Journal of Research -GRANTHAALAYAH, 2025)
Introduction: Phlebitis is derived from the Latin term Plebe, which means vein, and -itis, which means inflammation. Phlebitis is developed due to an inflammatory reaction in the vein, most commonly due to a thrombus. Aim: This study aim to assess the knowledge on phlebitis and its associated factors among nursing students in selected college of nursing, and association between knowledge on phlebitis and associated factors of phlebitis with demographic variables. Method: The investigator conducted a descriptive study on assessment of knowledge on phlebitis and its associated factors among 4th semester B.Sc nursing student . Conceptual framework of study was based on’ Health Belief Model, (Rosenstock,s 1974, Becker and Maiman,s 1975) revealed the relationship between a person’s belief and behaviour. Ninety B.Sc. nursing students (4th semester) were selected as samples by non-probability purposive sampling technique to collect data. A valid reliable structured knowledge questionnaire was used for data collection. Descriptive and inferential statistics were used for data analysis Result: The result revealed that the majority of 4th Semester B.Sc. nursing students obtained 80% average knowledge score on phlebitis and 72.22 % average knowledge score on associated factors of phlebitis. A significant association found between knowledge score of phlebitis and total duration of clinical exposure in weeks as chi- square value was 5.269 [3.841] at 0.05 level of significance. A significant association found between knowledge score of associated factors of phlebitis and total duration of clinical exposure in weeks as chi- square value was 3.946 [3.841] at 0.05 level of significance. The study has several implications in Nursing education, practice, administration, and research. The study concluded with recommendations for future intervention and improves policy implementation regarding phlebitis for reducing the infection.